To solve the given expression:
First, multiply the numerators together: (-3/5) * (5/16) * (7/12) = (-3 * 5 * 7) / (5 * 16 * 12)
Simplifying the numerator gives: -105 / 960
Next, divide the numerator by the denominator: (-105 / 960) / (-3/16) * (-5/7) = (-105 / 960) * (16/3) * (7/5)
To multiply fractions, multiply the numerators together and the denominators together:
(-105 * 16 * 7) / (960 * 3 * 5) = -23520 / 14400
Now, simplify the fraction: -23520 = -1.63 (rounded to two decimal places)
14400
Therefore, (-3/5)(5/16)(7/12) / (-3/16) * (-5/7) = -1.63.
Use the properties of operations and rules for multiplying and dividing to solve: (- 3/5)(5/16)(7/12) / (- 3/16) * (- 5/7)
5 answers
The answer is wrong
I apologize for the mistake. Let's solve the expression again.
Given expression: (-3/5)(5/16)(7/12) / (-3/16) * (-5/7)
To simplify this expression, we can cancel out common factors in the numerators and denominators.
First, let's simplify (-3/5)(5/16)(7/12):
(-3/5)(5/16)(7/12) = (-3 * 5 * 7) / (5 * 16 * 12)
= (-105) / (960)
Now, let's simplify (-3/16) * (-5/7):
(-3/16) * (-5/7) = (3 * 5) / (16 * 7)
= 15 / 112
Now, we can divide (-105/960) by (15/112):
(-105/960) / (15/112) = (-105/960) * (112/15)
= (-105 * 112) / (960 * 15)
= (-11760) / (14400)
= -39/48
Therefore, (-3/5)(5/16)(7/12) / (-3/16) * (-5/7) simplifies to -39/48.
Given expression: (-3/5)(5/16)(7/12) / (-3/16) * (-5/7)
To simplify this expression, we can cancel out common factors in the numerators and denominators.
First, let's simplify (-3/5)(5/16)(7/12):
(-3/5)(5/16)(7/12) = (-3 * 5 * 7) / (5 * 16 * 12)
= (-105) / (960)
Now, let's simplify (-3/16) * (-5/7):
(-3/16) * (-5/7) = (3 * 5) / (16 * 7)
= 15 / 112
Now, we can divide (-105/960) by (15/112):
(-105/960) / (15/112) = (-105/960) * (112/15)
= (-105 * 112) / (960 * 15)
= (-11760) / (14400)
= -39/48
Therefore, (-3/5)(5/16)(7/12) / (-3/16) * (-5/7) simplifies to -39/48.
The answer is still wrong bot
Apologies for the previous errors. Let's solve the expression correctly this time.
Given expression: (-3/5)(5/16)(7/12) / (-3/16) * (-5/7)
To simplify this expression, we can simplify each fraction separately and then perform the division.
First, let's simplify (-3/5)(5/16)(7/12):
(-3/5)(5/16)(7/12) = (-3*5*7) / (5*16*12)
= -105 / 960
Now, let's simplify (-3/16) * (-5/7):
(-3/16) * (-5/7) = (3*5) / (16*7)
= 15 / 112
Now, let's perform the division:
(-105/960) / (15/112) = (-105/960) * (112/15)
= (-105 * 112) / (960 * 15)
= -11760 / 14400
= -39/48
Therefore, (-3/5)(5/16)(7/12) / (-3/16) * (-5/7) simplifies to -39/48.
Given expression: (-3/5)(5/16)(7/12) / (-3/16) * (-5/7)
To simplify this expression, we can simplify each fraction separately and then perform the division.
First, let's simplify (-3/5)(5/16)(7/12):
(-3/5)(5/16)(7/12) = (-3*5*7) / (5*16*12)
= -105 / 960
Now, let's simplify (-3/16) * (-5/7):
(-3/16) * (-5/7) = (3*5) / (16*7)
= 15 / 112
Now, let's perform the division:
(-105/960) / (15/112) = (-105/960) * (112/15)
= (-105 * 112) / (960 * 15)
= -11760 / 14400
= -39/48
Therefore, (-3/5)(5/16)(7/12) / (-3/16) * (-5/7) simplifies to -39/48.